Different paths from transparency to trust? A comparative analysis of Finnish and Italian listed companies’ investor relations communication practices - Koskela, Merja; Crawford Camiciottoli, Belinda (Elsevier, 2020)
This paper investigates how companies seek to convey an image of transparency in their investor relations (IR) communication policy texts. It is based on two corpora compiled from texts describing the IR communication policies of companies listed on the Finnish OMX Helsinki 25 and the Italian FTSE MIB 40, representing two culturally different players within the European financial community. A two-pronged methodology was used to identify the linguistic and discursive expression of the concept of transparency: corpus-driven micro-linguistic analysis and rhetorical move analysis. Results showed that transparency and dialogue were keywords only in the Italian corpus. They further suggested that Finnish companies focus more on the efficient disclosure of information, whereas the Italian companies highlight their commitment to constant dialogue with stakeholders. The findings can be interpreted as reflecting cultural differences between the countries in terms of contextual vs. personal, affective vs. instrumental, and elaborate vs. exacting communication styles.
Keywords: investor relations; communication policy; transparency; trust; corpus methodology; rhetorical move analysis; cultural differences; enterprises; communication; information (communication); organisational communication and public relations; transparency; reporting; communication studies; science communication; companies (business enterprises); business; fi=Viestintätieteet|en=Communication Studies|